Architecture activism (Birkhäuser, 2016)
Entwerfen aus Verantwortung. Founded in Los Angeles in 1998, GRAFT is a global architectural practice which now maintains branches in Berlin and Beijing. The international practice, which is involved in architectural, urban, and product design – as well as branding – is known for its experimental and interdisciplinary designs as well as for its strong social commitment. The publication will document only projects characteristic of this social responsibility – it portrays architecture as an active tool for driving, in a global context, the development of places worth living in. One key project is the Solar Kiosk developed in 2012, a high-output, solar-based unit which is already used by many communities in Sub-Saharan Africa to secure their power supply